A systematic literature review of methodologies used for the design of serious games. A comparative analysis - Sandí Delgado, Juan Carlos (2020)
This article of systematic literature review presents the analysis of a series of methodological proposals, suggested for the design of educational video games. Nine different methodologies are analyzed. As part of the analysis, criteria are defined to describe and compare them, linked with the possibilities they have for the design of serious games. Criteria include: requirements elicitation and specification, pedagogical intention, pedagogical and ludic objectives definition, educational level and target public, roles identification, feedback type, user experiences analysis, objectives and methodologies validation. Main results indicate the following. 1) It is of vital importance, in the initial phase of a methodology design to incorporate the requirements elicitation and specification, as well as to define and assign roles of the different parties involved in the game production, all of this jointly and by consensus. 2) The definition of pedagogical objectives is closely related to the context use and it is important that it be done in the initial stage and then asses the game quality in the final stage. 3) It is important to incorporate the definition of pedagogical elements in the design. They will be helpful to assess the efficiency, learning and the user experience in relation with the interaction with the game. In addition, these pedagogical elements will facilitate the development of a quantitative record of learning to know the process and its quality by the user. It is concluded that the set of methodologies analyzed provide information in regards to the considerations when proposing a methodology for the design of a serious games. As a future work, there will be a methodological proposal, which will facilitate the integration of the aspects identified through the revision of the methodologies analyzed to guide systematically the design process of a serious game, specifically targeted to the teaching of digital competencies.